Community-based MDR-TB care project improves treatment initiation in patients diagnosed with MDR-TB in Myanmar. - Pyae Phyo Wai; Hemant Deepak Shewade; Nang Thu Thu Kyaw; Saw Thein; Aung Si Thu; Khine Wut Yee Kyaw; Nyein Nyein Aye; Aye Mon Phyo; Htet Myet Win Maung; Kyaw Thu Soe; Si Thu Aung (PLoS ONE, 2018)
The Union in collaboration with national TB programme (NTP) started the community-based MDR-TB care (CBMDR-TBC) project in 33 townships of upper Myanmar to improve treatment initiation and treatment adherence. Patients with MDR-TB diagnosed/registered under NTP received support through the project staff, in addition to the routine domiciliary care provided by NTP staff. Each township had a project nurse exclusively for MDR-TB and 30 USD per month (max. for 4 months) were provided to the patient as a pre-treatment support.To assess whether CBMDR-TBC project's support improved treatment initiation.In this cohort study (involving record review) of all diagnosed MDR-TB between January 2015 and June 2016 in project townships, CBMDR-TBC status was categorized as "receiving support" if date of project initiation in patient's township was before the date of diagnosis and "not receiving support", if otherwise. Cox proportional hazards regression (censored on 31 Dec 2016) was done to identify predictors of treatment initiation.Of 456 patients, 57% initiated treatment: 64% and 56% among patients "receiving support (n = 208)" and "not receiving support (n = 228)" respectively (CBMDR-TBC status was not known in 20 (4%) patients due to missing diagnosis dates). Among those initiated on treatment (n = 261), median (IQR) time to initiate treatment was 38 (20, 76) days: 31 (18, 50) among patients "receiving support" and 50 (26,101) among patients "not receiving support". After adjusting other potential confounders (age, sex, region, HIV, past history of TB treatment), patients "receiving support" had 80% higher chance of initiating treatment [aHR (0.95 CI): 1.8 (1.3, 2.3)] when compared to patients "not receiving support". In addition, age 15-54 years, previous history of TB and being HIV negative were independent predictors of treatment initiation.Receiving support under CBMDR-TBC project improved treatment initiation: it not only improved the proportion initiated but also reduced time to treatment initiation. We also recommend improved tracking of all diagnosed patients as early as possible.